2018
DOI: 10.1002/awwa.1143
|View full text |Cite
|
Sign up to set email alerts
|

Using Historical LCR and Water Quality Data to Evaluate Corrosion Control Treatment

Abstract: Historical Lead and Copper Rule (LCR) regulatory sampling data from the Philadelphia Water Department were examined to explore their potential value for guiding a water utility's progress with regard to optimal corrosion control treatment (OCCT). If a system has established a stable water treatment process with consistent corrosion control treatment (CCT) and has achieved continued decreases in lead levels during regulatory sampling, then the information collected during LCR monitoring can be used as an import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…The results from both demonstration studies indicate a point of diminishing returns at higher orthophosphate doses. These findings are consistent with lead solubility models shown in Figure 6 as well as other studies that have found diminishing returns for especially above 1.5-2 mg/L as PO 4 in the pH 7-8 range (Bradley & Horscroft, 2018;Cardew, 2009;Schock, 1980;Schock et al, 1996;Schock & Gardels, 1983;Wahman et al, 2021).…”
Section: Comparison Of Orthophosphate Treatment In Coupon and Pipe Ra...supporting
confidence: 92%
See 1 more Smart Citation
“…The results from both demonstration studies indicate a point of diminishing returns at higher orthophosphate doses. These findings are consistent with lead solubility models shown in Figure 6 as well as other studies that have found diminishing returns for especially above 1.5-2 mg/L as PO 4 in the pH 7-8 range (Bradley & Horscroft, 2018;Cardew, 2009;Schock, 1980;Schock et al, 1996;Schock & Gardels, 1983;Wahman et al, 2021).…”
Section: Comparison Of Orthophosphate Treatment In Coupon and Pipe Ra...supporting
confidence: 92%
“…In addition, the average sulfate and total dissolved solids concentration at Marston was 2 times higher than at Moffat (Table 1). Other studies have also found that blending of treated water from different sources in the drinking water distribution system can increase metals release which may explain the phenomenon observed in this study (Bradley & Horscroft, 2018;Zhang et al, 2018). Because all operational parameters were maintained during this period and this is a normal occurrence, these data were included in the analysis.…”
Section: Lead Release In Ph Adjustment and Orthophosphate Pipe Racksmentioning
confidence: 81%
“…WLLs in key concentration ranges for selected utilities and for all utilities in groups 1, 2, and 4 are shown in Table . This type of visualization has been used successfully in other studies to investigate the efficacy of CCT. , 95% of WLLs for group 1 systems are less than or equal to 5 ppb, compared to 81.1% of group 2 systems. Systems in compliance group 1 are likely to have a lower percentage of lead results in the 5–15 ppb range than group 2 systems.…”
Section: Looking Beyond the Lead 90th Percentile Action Levelmentioning
confidence: 99%
“…In addition to phosphorous impact on the amount of copper corrosion in the system, increased phosphorous concentrations can promote increased nitrification during periods of stagnation, as phosphorous is a key nutrient for nitrifying bacteria [123]. Some utilities use zinc orthophosphate for corrosion control [125,126] and the combination of zinc and copper at moderate levels may provide increased stability for monochloramine and reduce nitrification levels [123,127,128].…”
Section: Corrosionmentioning
confidence: 99%